Investment and Uncertainty: A Theory-Based Empirical Approach - Mikael Carlsson (Uppsala University, Department of Economics, 2004)
This paper provides empirical evidence on the dynamic effects of uncertainty on firm-level capital accumulation. A novelty in this paper is that the firm-level uncertainty indicator is motivated and derived from a theoretical model, the neoclassical investment model with time to build. This model also serves as the base for the empirical work, where an error-correction approach is employed. I find a negative effect of uncertainty on capital accumulation, both in the short and the long run. This outcome cannot be explained by the model alone. Instead, the results suggest that the predominant mechanism at work stems from irreversibility constraints.
Keywords: C33; D21; D80; E22; 330; Investment; Uncertainty; Dynamic Panel Data Models; Geldpolitik; Regelbindung; Zins; Preisrigidität; Taylor-Regel; Theorie; Gleichgewicht